Molecular detection of Coxiella burnetii in raw meat intended for pet consumption. (29th April 2020) - Shapiro, Amanda; Bosward, Katrina; Mathews, Karen; Vincent, Gemma; Stenos, John; Tadepalli, Mythili; Norris, Jacqueline
Abstract: The discovery of antibodies against Coxiella burnetii in cattery‐confined breeding cats indicating prior or current exposure (Shapiro et al., 2015) prompted an investigation into possible sources of infection. One hypothesis was that raw meat diets containing reservoir species may provide a source of C. burnetii transmission. The aim of this pilot study was to determine whether C. burnetii DNA was present in raw meat sold exclusively for companion animal consumption. The sample population consisted of raw meat packages ( n  = 58) of primarily kangaroo origin, with three to four aliquots (50–120 mg) randomly selected from each package. Genomic DNA was extracted from whole tissue in each of these aliquots using a modified protocol. Three quantitative PCR assays were used for the detection of C. burnetii targeting the IS 1111 gene, the heat shock operon htpAB and the C. burnetii outer membrane protein‐coding gene, com1 . Coxiella burnetii DNA was detected in 25/58 samples (43%) using the IS 1111, htpAB and/or com1 PCR assays and confirmed by DNA sequencing. All samples amplifying a product in the com1 assay also amplified a product in the htpAB and IS 1111 assays. A total of 17/58 (29%) packets were positive with all three genes, 4/58 (7%) were positive with two genes (IS 1111 and htpAB ) and 4/58 (7%) were positive with the IS 1111 gene only. Coxiella burnetii DNA was five times more likely to be found in offal than skeletal muscle meat samples. All meat samples in which C. burnetii DNA was found were from kangaroo tissues, while samples labelled as non‐kangaroo meat ( n  = 4) were negative. Multi‐locus variable number of tandem repeat analysis (MLVA) identified three different genotypes of C. burnetii that have all been identified previously from Australian human clinical Q fever cases. Further investigations are required to determine the potential role of certain raw meats in the transmission of C. burnetii to cats and humans.